2009
DOI: 10.1590/s1516-89132009000100027
|View full text |Cite
|
Sign up to set email alerts
|

Anthropic influence in the water quality of the river basin that supplies the Pato Branco Municipality-PR

Abstract: The Pato Branco river basin, which supplies water to Pato Branco city (70,000 inhabitants) ). The lowest and the highest variation coefficients for data downstream and upstream corresponded to: nitrate and nitrite (46.1 and 166%); phosphorous and nitrite (56.8 and 229.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
3
1
0
1
Order By: Relevance
“…These sites had greater urban occupation and deeper riparian forest degradation than in all other sites we sampled. Our results are similar to those results found in studies from other regions (Mota, 1995;Sabater et al, 1996;Agatz et al, 1999;Sonnemann et al, 2001;Brito et al, 2005;Salomoni et al, 2007;Marotta et al, 2008;Machado et al, 2009, Cunha et al, 2010.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These sites had greater urban occupation and deeper riparian forest degradation than in all other sites we sampled. Our results are similar to those results found in studies from other regions (Mota, 1995;Sabater et al, 1996;Agatz et al, 1999;Sonnemann et al, 2001;Brito et al, 2005;Salomoni et al, 2007;Marotta et al, 2008;Machado et al, 2009, Cunha et al, 2010.…”
Section: Discussionsupporting
confidence: 93%
“…Chapman and Kimstach (1996) ; when COD values reach 200 mg.L -1 they are considered to be receptors of pollution sources. These results support other studies that demonstrate that urbanization interferes with water quality (Karn and Harada, 2001, Ouyang et al, 2006, Salomoni et al, 2007, Machado et al, 2009.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on these data, it was found that the limit of 3.7 mg L -1 established by Conama Resolution nº 375/05 (CONAMA, 2005) for total nitrogen was exceeded on only two occasions: October 2016 (5.8 mg L -1 ) and October 2018 (6.3 mg L -1 ). Regarding the total phosphorus content, Machado et al (2009) mentions that in rivers with low currents, the critical levels of phosphorus to start the eutrophication process are in the range of 0.1 to 0.2 mg L -1 , while in rivers of high current, it should not exceed the limit of 0.3 mg L -1 . Data collected for the Una River reveal that this limit was also exceeded on only two occasions: in October 2010 (0.5 mg L -1 ) and December 2013 (1.2 mg L -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Os parâmetros nitrogenados também tenderam a crescer com o volume precipitado, com exceção do ponto BR-2, que representa o ponto mais crítico em termos de poluição, situado logo após o núcleo urbano de Lages. O aumento pode estar relacionado com a ocorrência de áreas agrícolas, indicando um aporte de formas nitrogenadas oriundas de adubações de culturas anuais levadas ao rio pelo escoamento superficial, fato também constatado por (Machado, Becegato, Bittencourt, 2009) estudando a bacia do rio Branco, PR. No caso do ponto BR-2 as correlações negativas indicam a diluição das mesmas.…”
Section: Efeito Das Precipitações Sobre Os Parâmetros Analisadosunclassified